Current and future burden trends of lip and oral cavity cancer based on estimated annual percentage change and the Bayesian age-period-cohort model: a study based on the global burden of disease 2021 - Mu, Qiong-Ying; Min-Li,; Chen, Si-Wen; Tang, Sheng-Rong (Frontiers in Oncology, 2025)
IntroductionLip and Oral Cavity Cancer (LOCC), as a common type of malignant cancer, has become an important public health issue. This study aims to analyze and predict the trend of the LOCC burden, providing guidance for reducing the burden of LOCC.MethodsThis study was based on the Global Burden of Disease (GBD) database 2021. We assessed the differences in LOCC among different regions and sexes from 1990 to 2021 using Age-Standardized Rates (ASR) and Estimated Annual Percentage Change (EAPC). Additionally, Bayesian Age-Period-Cohort (BAPC) model was employed to predict the Incidence, Prevalence, Death, Disability-Adjusted Life Years (DALYs), Years of Life Lost due to disease (YLLs), and Years Lived with Disability (YLDs) of LOCC globally from 2022 to 2030.ResultsFrom 1990 to 2021, the global ASR of Incidence (ASIR), ASR of Prevalence (ASPR), and ASR of YLDs for LOCC had significantly increased, while the ASR of Death (ASDR), DALYs, and YLLs had decreased. The BAPC model predicted that by 2030, the ASIR and ASPR for males would decrease, while for females, an upward trend would be observed. The middle-aged and elderly population (>50 years) would still be the main patient group (accounting for over 60%).ConclusionThe disease burden of LOCC remains severe at present, but it is expected to show a downward trend by 2030. Therefore, it is still necessary to intensify efforts in the prevention and control of LOCC to achieve the expectation. This study provides theoretical guidance for reducing the burden of LOCC.